Características clínicas e fenotípicas de asma grave resistente à terapia em crianças brasileiras - Rodrigues, Andréa Mendonça (2014)
Introduction: Studies of children with severe therapy-resistant asthma are scarce in developed countries and there is no published data about clinical presentations and characteristics of these patients in developing countries. Objective: To describe the main clinical characteristics, lung function, radiological findings, and inflammation of induced sputum of children with severe therapy-resistant asthma from a reference center in southern Brazil. Methods: Children between 6-14 years of age, followed by at least 6 months in a reference center, with severe therapy-resistant asthma (uncontrolled asthma using elevated doses of inhaled corticoid associated with long-acting beta-2 agonist) were retrospectively selected. All subjects from the reference center had clinical data, disease control, lung function, skin test reactivity to aeroallergens, inflammation of induced sputum, chest computerized tomography, and pH esophageal monitoring results prospectively collected. Results: 21 patients were selected (mean age: 9.2 yo). Eighteen patients (86%) were atopic. Most patients presented uncontrolled disease during most visits, with nearly normal baseline lung function parameters. The sputum of two patients were paucigranulocytic, 4 were eosinophilic and 7 neutrophilic, where 67% of the children who repeated sputum exam changed the inflammatory patterns. 6/7 (86%) of the children who were treated with omalizumab (anti-IgE) showed improvement in quality of life, with an important reduction in exacerbations and hospitalizations. Conclusions: Most children with severe therapy-resistant asthma from a non-affluent population were patients with difficult-to-control disease, with nearly normal lung function and prone to change airway inflammatory pattern during follow-up, most of them atopics. This profile, unlike adults, need to be better understood in relation to the mechanisms that result in symptoms unresponsive to optimized drug therapies.